The Kajve Initiative: Establishing a Holistic Intervention Model for Prosperous Smallholder Livelihoods and Sustainable Supply Chains - Filippo Maggioni; Rosa Inés Gonzalez Torres; Elisabeth von der Ohe (Proceedings)
In 2019, the voluntary initiative “Kajve” was established to improve the quality of life of smallholders in Chiapas, a hotspot for Mexican production where coffee often represents the main income source yet low production often keeps households below the poverty line. The initiative’s ambition is to jointly address the issues of low incomes, climate change vulnerability, and yield-threatening diseases, as well as ecosystem degradation due to deforestation, to promote more sustainable supply chains while respecting the legacy of indigenous communities. To date, Kajve has reached over 1500 growers across 37 indigenous communities partly situated within biosphere reserves. The initiative’s efforts rest upon collaboration with institutional and private partners and participatory dialog with growers and their communities. Trainings and extension visits covering Good Agricultural Practices, environmental education, and plantation renovation were offered in cooperation with UNESCO and value chain partners. The former characterized the value of traditional coffee farming practices in a baseline assessment, ensuring culturally appropriate methods that respect the ethnic components underlying coffee cultivation. The initial results highlight up to a 35% increase in coffee yields, a 98% reduction in rust incidence, and an improvement of over two points in cup quality. The initiative currently works with the International Center for Tropical Agriculture (CIAT) and Solidaridad Network to implement and assess high-productivity agroforestry system design; complementary interventions for multifunctional landscapes, including replanting native species and water retention structures; circular resource management (e.g., composting, efficient inorganic nutrient application, and coffee wastewater treatment); and the management of pests and diseases leveraging BASF technology. The current challenge is to complete the Kajve intervention model with commitment by actors in the value chain—creating the economic incentive to empower growers to secure their own prosperity while achieving truly sustainable coffee production.